Pengaruh Faktor Ekonomi Terhadap Pendapatan Petani Sawah (Studi Kasus Kelurahan Pettuadae Kecamatan Turikale Kabupaten Maros) - Suryani Suryani; Mohammad Anwar Sadat; Azisah Azisah (Jurnal Agribis, 2021)
This research was conducted in Pettuadae Village, Turikale District, Maros Regency. The economic factors that each farmer has are different. This will be related to the capacity of farmers in generating production and farm income. The purpose of this study is to analyze the influence of economic factors on the income of rice farmers. The research method used is descriptive analysis method. The data used are primary data and secondary data.The result of the study concluded that farmers’ economic faktors (land area of labor and farm costs) simultaneously had a significant effect on income, while only partially, land area had a significant effect on farmers’ income.